Contribution to the knowledge of the Papilionoidea fauna of Dhofar (Sultanate of Oman) (Insecta: Lepidoptera) - R. Verovnik; M. Seizmair; V. Hula; Z. Mrácek; Z. F. Fric (SHILAP)
The Lepidoptera fauna of Dhofar province and Sultanate of Oman in general have been poorly studied with a total of 63 species recorded so far for the province. Our aim was to study the distribution of Lepidoptera more in detail, in particularly for some rare species with limited records. We sum up the results of 13 expeditions to Dhofar in the period between 2008 and 2019. Lepidoptera were recorded from 67 localities covering mostly the three mountain ranges in the region. Among 65 species recorded Colias crocea (Geoffroy, 1785) is new for the country and three are new for the region (Papilio machaon muetingi Seyer, 1976, Papilio demoleus Linnaeus, 1758 and Pelopidas thrax (Hübner, [1821])) bringing the total to 72 species recorded for Dhofar. Additionally, interesting records for the following species are discussed in detail: Colotis liagore (Klug, 1829), C. protomedia (Klug, 1829), Acraea neobule Doubleday, 1847, Melitaea deserticola scotti Higgins, 1941, Melanitis leda (Linnaeus, 1758), Cigaritis dhofarina Seizmair, 2017, Chloroselas esmeralda bilqis Larsen, 1983, Tarucus balkanicus (Freyer, 1844), Azanus moriqua (Wallengren, 1857), Euchrysops lois (Butler, 1886), Spialia colotes semiconfluens de Jong, 1978, and Spialia zebra bifida (Higgins, 1924). Further surveys during monsoon season would be valuable to complement our study.